Periodontal health in a large cohort of Ugandans living with HIV: a cross-sectional study - William Buwembo; Adriane Kamulegeya; Dunstan Kalanzi; Priscilla Naava Namuyonga; Proscovia Nakasujja; David P. Katete; F. Collins Semitala; Catherine Mwesigwa-Lutalo; Samuel Kalungi; Jennifer E. Cameron; Ian G. Munabi (BMC, 2024)
Abstract Background The impact of periodontitis on large populations of people living with HIV (PLHIV) in resource-constrained settings remains largely un-investigated. This study aims to address this knowledge gap by providing a comprehensive description of the periodontal health status among a sizable cohort of Ugandans living with HIV. Methods This was a cross-sectional study with 4,449 participants who were over 18-years old with data captured on their reported age, gender, tobacco use, length of time on HAART and alcohol use. Periodontal health was assessed using the WHO periodontal probe and the modified CPI data entry form. Descriptive statistics were reported using frequencies for the affected number of sextants in the surveyed participants. This was followed by additional regression analysis using the R statistical computing environment, with the periodontal health outcomes (bleeding on probing, pocket depth and clinical attachment loss) individually as the dependent, recorded as binary outcomes. A multilevel model was run with clinical attachment loss as the dependant variable controlling for all the other factors. The 95% confidence intervals were used to report the level of significance for each test. Results There were 3,103/4,449 (69.7%) female participants. The mean age was 44.3 years (SD 10.1 years) with a range of 18 to 89 years. About 66% of the participants had bleeding on probing at one or more of the examined sites/tooth surfaces. The odds for bleeding on probing were significantly higher for female participants (adjusted Odds ratio: 1.49, 95% CI 1.19 to 1.86), and higher in individuals who reported tobacco use (adjusted odds ratio 1.62, 95% CI 1.09 to 2.41). Slightly under half of our participants (48.2%) had moderate to severe clinical attachment loss. Conclusions This study found that among Ugandans living with HIV, periodontal disease is a significant public health concern. The majority of study participants had bleeding on probing and almost half of them recording moderate to severe clinical attachment loss, worsened by age and time on HAART. This highlights the need for comprehensive oral health care and targeted interventions for this population.